I crawl through it - King, A. S. (Amy Sarig), 1970- (Little, Brown and Company, 2015)
Four teenagers are on the verge of exploding. The anxieties they face at every turn have nearly pushed them to the point of surrender: senseless high-stakes testing, the lingering damage of past trauma, the buried grief and guilt of tragic loss. They are desperate to cope, but no one is listening. So they will lie. They will split in two. They will turn inside out. They will even build an invisible helicopter to fly themselves far away... But nothing releases the pressure. Because, as they discover, the only way to truly escape their world is to fly right into it.